System of Environmental Governance in the Sun Bear Conservation Area in KWPLH Balikpapan City - Hermawan, Dede Augustira; Sudaryono, Sudaryono (Universitas Ibn Khaldun Bogor, 2023)
The existing environmental management system in a conservation area containing wild animals, in this case the sun bear, has so far been managed by the Environmental Education Tourism Area (KWPLH) and needs more support to realize all the plans and developments that have been prepared by the management. . One of the efforts presented in this study to provide support to the manager is to provide a perspective from an external party. How far has the management of governance been carried out by KWPLH in carrying out the plans they have made. Of course this can be new ammunition for the managers in their journey to develop this tourist area. With this research, KWPLH can help find out what things they still lack or haven't done in developing this tourist area. Research that focuses on examining this has never been done before. Not only the development of the area, but also the maintenance of this conservation area will be discussed. In addition to knowing the shortcomings of the manager so far in managing this conservation area, the manager can also find out what advantages they have done for this sun bear habitat. The habitat of the sun bear is one of the assets that must be properly guarded considering that physical development is increasingly widespread in urban areas with the aim of development that can prosper and prosper people's lives, but in the development process it has caused its own problems because there are plans that are considered to be still not good or enough.